Patient Experiences of Digital Technology Use in Interstitial Lung Disease (PRODIGY-ILD Study): Qualitative Study Using Reflexive Thematic Analysis - Emer Gunne; Alessandro Franciosi; Cormac McCarthy; Michael P Keane; Peter Doran; Sinead Holden (JMIR Human Factors, 2026)
Abstract Background Digital health technology enables collection of continuous physiological and behavioral data from participants in clinical trials. This supports hybrid trial designs, potentially reducing clinic visits and participant burden for patient monitoring. Interstitial lung disease (ILD) is characterized by an unpredictable clinical course, creating a need for new treatments and more sensitive approaches to assessing treatment effectiveness, disease progression, and clinically meaningful trial end points. Objective This study aimed to explore the experiences of individuals with ILD using digital tools in a clinical study to inform digital health–enabled clinical research. Methods This qualitative study was conducted within the PRODIGY-ILD (Predicting Outcomes using Digital Technology in Interstitial Lung Disease) cohort, a prospective observational study using wearable devices and electronic patient-reported outcome measures for a planned 3 years of longitudinal monitoring. Participants were recruited from a specialist outpatient ILD clinic. A topic guide was developed iteratively, and individual semistructured interviews were conducted remotely via Zoom (Zoom Video Communications, Inc) and/or telephone, audio-recorded, and transcribed. Data were analyzed using reflexive thematic analysis with NVivo software (Lumivero). Results Fifteen of the final 20 participants recruited to the PRODIGY-ILD study consented and completed interviews. Four key themes were identified, highlighting how trust, digital literacy, participant-initiated engagement with data, and illness burden shape sustained participation in digital health–enabled clinical research: (1) trust and altruism override data concerns: confidence in researchers’ data handling and a desire to contribute enabled data sharing; (2) navigating digital tools: friction and flexibility: digital literacy, usability, and device compatibility varied, but participants were able to use workarounds to maintain engagement; (3) participant-initiated engagement with wearable data: participants moved from passive to active engagement, in many cases integrating devices into daily routines; and (4) life-limiting illness as a constraint on digital trial participation: managing symptoms and severe comorbidities reduces motivation and engagement with study technology. Conclusions Despite participants’ motivations to contribute data to research, engagement was shaped by usability, participant-initiated engagement, and the constraints of living with chronic illness. There is a need for patient-centered design, tailored support, and flexible trial procedures to optimize adherence in digital health–enabled clinical research.